School-based health promotion to improve mental health literacy: a comparative study of peer- versus adult-led delivery. (2nd January 2023) - Booth, Ailbhe; Doyle, Elizabeth; O'Reilly, Aileen
Abstract: Background: School-based youth mental health promotion is increasingly recognised as a useful tool to improve mental health knowledge and help-seeking among adolescents. Peer-led initiatives are emerging as a potentially viable mode of delivering this material. Yet, there is limited evidence on the effectiveness of these initiatives compared to more traditional, adult-led, forms of mental health promotion. Aims: This study aimed to compare improvements in students' mental health knowledge and help-seeking after attending either a peer- or adult-led youth mental health promotion workshop. It also sought to examine differential effects by gender. Method: A within- and between-group comparative design was used to examine secondary school students' ( N  = 536) mental health knowledge and help-seeking intentions before and after attending a school-based mental health promotion workshop. Results: Students' mental health knowledge and help-seeking intentions significantly improved in both peer- and adult-led groups. Outcomes did not differ across modes of delivery, although the impact of adult-led workshops on mental health knowledge was moderated by gender. Conclusions: Peer-led youth mental health promotion appears to be as effective as traditional adult-led delivery, and seems to be particularly beneficial for male students who respond more favourably to content communicated through their peers.